Improvement in emulsifying properties of soy protein isolate by conjugation with maltodextrin using high‐temperature, short‐time dry‐heating Maillard reaction. (3rd September 2013) - Zhang, Jinbo; Wu, Nana; Lan, Ting; Yang, Xiaoquan
Summary Soy protein isolate (SPI)–maltodextrin (MD) conjugates were synthesised using Maillard reaction under high‐temperature (90, 115 and 140 °C), short‐time (2 h) dry‐heating conditions. The loss of free amino groups in proteins and sodium dodecyl sulphate polyacrylamide gel electrophoresis (SDS‐PAGE) profile confirmed that SPI‐MD conjugates were formed and higher dry‐heated temperatures could increase the glycosylation degree. The emulsifying properties of SPI and SPI‐MD conjugates were evaluated in oil‐in‐water emulsions. The emulsions stabilised with SPI‐MD conjugates synthesised at 140 °C exhibited higher emulsifying stability and excellent storage stability against pH, ionic strength and thermal treatment compared with those synthesised at 90 °C, 115 °C and SPI stabilised emulsions. This might be due to a greater proportion of conjugated MD in SPI‐MD conjugates synthesised at 140 °C because of the higher glycosylation degree, and more conjugated MD on the droplet surface could provide steric effect and enhance the stability of the droplets in the emulsions.